Experiences of change following a blended intervention for adults with ADHD and emotion dysregulation: a qualitative interview study - Emilie S. Nordby; Viktor Schønning; Alice Barnes; Hayley Denyer; Jonna Kuntsi; Astri J. Lundervold; Frode Guribye (BMC Psychiatry)
Abstract Background Emotion dysregulation commonly co-occurs with attention-deficit hyperactivity disorder (ADHD), leading to a range of negative outcomes. While psychological interventions have shown promise in bringing about positive changes in emotional and cognitive domains, there is still limited knowledge on the subjective experiences of change among the participants in these interventions. Aim The present study explores the experiences of adults with ADHD who had participated in a blended digital and face-to-face intervention aimed at improving emotion dysregulation. The study focuses on understanding their experiences of change and identifying contributors to change. Methods A total of 9 adults with ADHD participated in individual semi-structured, in-depth interviews following their participation in the intervention. The interviews were analyzed using thematic analysis. Results The thematic analysis resulted in three core themes. The first theme, ‘perceiving change’, represents changes that the participants experienced, with four subthemes: 1a) being in control, 1b) feeling aware, 1c) accepting oneself and one’s emotions and 1d) gaining insight and knowledge. The second theme, ‘supporting change’, captures factors that supported the participants’ changes, with five subthemes: 2a) acquiring skills, 2b) being in it together, 2c) therapist guidance, 2d) finding motivation 2e) putting it into practice. Lastly, the third theme, ‘sustaining change’, includes aspects important to maintain change, with two subthemes: 3a) working consistently and 3b) giving it time. Conclusions The findings show that the participants experienced various changes related to the management of their emotions following their participation in the intervention. Change was perceived as a multifaceted process, supported by internal factors such as motivation and engagement, along with external factors such as support from the other group members and the therapists. Taken together, the findings from the study could be important to the development of psychological interventions for adults with ADHD and may provide valuable knowledge to clinicians and policymakers. Trial registration Registered on 21st November 2022 at ClinicalTrials.gov. ClinicalTrials.gov ID: NCT05644028.